A study on suicidal ideation and depression among patients attending out patient department (OPD) of Community Medicine and General Medicine at a tertiary care hospital in Kolkata - Sanjay Kumar Saha; Ankita Mishra; Kuntala Ray; Meghna Mukherjee; Soumit Roy; Mausumi Basu (Al Ameen Medical College, 2022)
Background: There has been a rampant increase in the number of suicides of late, especially in those suffering from depression. Objectives: To assess the suicidal ideation and depression among the patients visiting the Out Patient Department (OPD) of a tertiary care hospital and to study their association with each other and with other variables. Materials and Methods: A descriptive type of observational study, cross-sectional in design was conducted among 157 patients attending the Community Medicine and General Medicine OPD at IPGME&R and SSKMH, Kolkata from November to December, 2019. The tool employed was a predesigned, pretested, structured schedule which included Suicidal Ideation Scale and Patient Health Questionnaire-9 (PHQ-9). Data were analyzed using descriptive and inferential statistics. Results: About 75% participants had mild to severe depression while 50.3% had suicidal ideation. Education and socio-economic status had statistically significant association with depression while age, gender, education, employment, socio-economic status, domestic violence, acute trauma and depression were associated with suicidal ideation. Conclusion: Depression and suicidal ideation were a major burden among the patients attending the Community Medicine and General Medicine Out Patient Department in Kolkata. Presence of moderate to severe depression increased the risk of suicidal ideation.